Optimizing The Management of Zakat on Income: Case Study of BAZNAS Bogor Regency - Sa'dul Hayyi; Muhammad Fahri Farid; Muhammad Hasbi Zainal (Department Islamic Economics, 2024)
In Bogor Regency, zakat on income presents a significant opportunity for BAZNAS to enhance zakat optimization, with a potential of Rp. 75 billion within one year from ASN Bogor Regency alone. However, in 2021, only 18.7% of this potential was collected, involving just 5,700 out of 19,000 civil servants. This thesis aims to address three key objectives: 1) Examine zakat management at the National Amil Zakat Agency in Bogor Regency, 2) Analyze the outcomes of ASN income zakat at the same agency, and 3) Identify supporting and inhibiting factors in the management of ASN income zakat in Bogor Regency. The research, utilizing normative and socio-religious approaches, involved fieldwork with data collected through library research, observation, interviews, and documentation. Findings revealed suboptimal zakat management at the agency, with a lack of awareness among civil servants regarding professional zakat systems. The study also highlighted supporting factors like the potential of professional zakat, government support, and zakat as a Muslim obligation, alongside inhibiting factors such as insufficient quantity and quality of zakat managers, suboptimal government involvement, and low civil servant awareness